2021
DOI: 10.9767/bcrec.16.3.9739.446-458
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Yeast Microbial Fuel Cell Integrated with Sugarcane Bagasse Fermentation for COD Reduction and Electricity Generation

Abstract: The purpose of this analysis is to evaluate the efficiency of the Microbial Fuel Cell (MFC) system incorporated with the fermentation process, with the aim of reducing COD and generating electricity, using sugarcane bagasse extract as a substrate, in the presence and absence of sugarcane fibers. There is a possibility of turning bagasse extract into renewable bioenergy to promote the sustainability of the environment and energy. As a result, the integration of liquid fermentation (LF) with MFC has improved eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…The main purpose of this section is to determine the best values of the glucose concentration and glucose/yeast ratio to maximize the output power of YMFC. The decision variables' upper and lower boundaries are set to [15,10] and [5,1]. These figures are derived from measured data.…”
Section: Optimization Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main purpose of this section is to determine the best values of the glucose concentration and glucose/yeast ratio to maximize the output power of YMFC. The decision variables' upper and lower boundaries are set to [15,10] and [5,1]. These figures are derived from measured data.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…where, f (X) is the fuzzy model's output; X = [x 1 , x 2 ] are the input parameters, which varied in the ranges x 1 ∈ [5,15] and…”
Section: Fuzzy Based Model Of Ymfcmentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidation releases electrons, decreasing the number of carbon atoms and transforming acetate into acetyl-CoA for the Krebs cycle. Electron Transfer Chain activation uses high-energy molecules for redox reactions ( Christwardana et al, 2021 ).…”
Section: Biological Methods and Mechanism Of Degradationmentioning
confidence: 99%
“…Hence, in a given time period, microbes can use acetic acid more efficiently than the more complex substrates, and generate the greatest number of electrons (producing more voltage). A previous study [32] evaluated the possibility of bagasse as a substrate to produce voltage along with COD reduction in an MFC under anaerobic conditions. The authors indicated the possibility of converting bagasse extract into sustainable bioenergy.…”
Section: Electron and Voltage Generation In The Mfcmentioning
confidence: 99%